Multiple early local transmissions of chikungunya virus, Mainland France, from May 2025 - Clémentine Calba (Eurosurveillance)
In 2025, a large outbreak of chikungunya occurred in Réunion Island (France). By 10 July, 1,911 imported cases were notified in Mainland France, most (89%) were associated with travel to Réunion Island. Ten autochthonous outbreaks in five French regions involving 27 cases were identified between May and mid-July and outbreaks occurred earlier than in previous years. Aedes albopictus, the mosquito vector, is endemic in large parts of France. Transmission events early in the vector active season is concerning.